Analisis Pengaruh Belanja Infrastruktur Pekerjaan Umum Terhadap Tenaga Kerja Yang Terserap dan Pertumbuhan Ekonomi di Indonesia Tahun 2011 - 2015 - B2052162008, Muhamad Arvip (Jurnal Ekonomi Daerah (JEDA), 2019)
ABSTRACTÂ This study aims to examine and analyze the effects of the public works infrastructure expenditure on labor absorption and economic growth in Indonesia in 2011-2015. The study had been conducted for five years from 2011 to 2015 by using secondary data provided by the Ministry of Public Works and Public Housing, and Central Bureau of Statistics in the form of combination between times series data (from 2011 to 2015) and cross-sectional data (33 province in Indonesia) which also known as panel data.The hypothesis was examined by using fixed effects model from EViews statistics application. The test result shows the level of significance =0,05. The result shows that first, the government expenditure on water resources division has a positive and significant effect on labor absorbtion and economic growth. Second, the government expenditure on Bina Marga division has a negative and not significant effect on labor absorbtion but has a positive and not significant effect on economic growth. Third, the government expenditure on Cipta Karya division has a positive and significant effect on labor absorbtion but a negative and significant effect on economic growth. Fourth, labor absorbtion has a positive and significant effect on economic growth. Â Keyword : Public Works Infrastucture, Water Resources Division, Bina Marga Division, Cipta Karya Division, Labor Absorbtion, and Economic Growth.